The new violent cartography : geo-analysis after the aesthetic turn - Opondo, Samson Okoth; Shapiro, Michael J. (Interventions (Routledge (Firm))., 2012)
"This edited volume will collect a number of essays which propose and examines different though related critical responses to modern cultures of war among other cultural practices of statecraft. Taken together, these essays present a space of creative engagement with the political and draw on a broad range of cultural contexts and genres of expressions to provoke the thinking that exceeds the conventional stories and practices of international relations"--